Mechanistic assessment of the analgesic, anti-inflammatory and antipyretic actions of Dalbergia saxatilis in animal models - Omoniyi K. Yemitan; Olufunmilayo O. Adeyemi (Taylor & Francis Group, 2017)
Context: Aqueous root extract of Dalbergia saxatilis, Hook, f., (Leguminosae) (DS) is reported useful for toothache, pains, and fever, but not scientifically proven. Objective: This study determined its effectiveness in pain, inflammation, and fever, applying scientific models. Materials and methods: Swiss mice or Sprague-Dawley rats (n = 5) were pretreated with distilled water, DS (100 or 200 mg/kg), or standard drug for 30 min. The analgesic activity was measured by acetic acid writhing, tail flick, tail immersion, tail clip, hot plate, and formalin pain tests; anti-inflammatory effects were determined via carrageenan and dextran rat paw oedema tests; antipyretic activity was measured by Escherichia coli lipopolysaccharide (ECL) and turpentine in rabbits, and d-amphetamine sulphate (d-AS) pyrexia test in rats. Results: Writhing frequency inhibition was produced by 200 mg/kg DS (33.10%), aspirin (38.19%) and morphine (93.68%). Unlike morphine, DS did not produce significant prolongation of the reaction times in the hot-plate, tail immersion, tail flick, and tail clip tests. In the first and second phases of formalin test, respectively, % inhibition was: 200 mg/kg DS (25.70% and 0%), aspirin (4.76% and 67.33%), morphine (81.42% and 66.11%); for carrageenan and dextran tests, significant difference was recorded between 200 mg/kg DS and control up to 6 h. Significant reduction in ECL, turpentine and d-AS pyrexia was recorded at 100 and 200 mg/kg DS. Conclusion: DS produces mild non-steroidal analgesic and anti-inflammatory, as well as significant antipyretic actions involving cyclooxygenase, α2 adrenoceptor and interleukin-1 β1 due to any of glycosides, saponins or phenolic tannins.